Covid-19: The communication needs of D/deaf healthcare workers and patients are being forgotten. (15th June 2020) - Grote, Helen; Izagaren, Fizz
Abstract : We need to ensure that in our response to covid-19, the rights of those with hearing loss are not forgotten, say Helen Grote and Fizz Izagaren